Thromboelastography Values from Pigtail Macaques (Macaca nemestrina): Effects of Age and Sex - Fong, Derek L (American Association for Laboratory Animal Science, 2012)
Thromboelastography is a clinical laboratory test used to assess global hemostasis. With technologic advances and the test's reemergence in human medicine, its utility in veterinary medicine is being explored. Because assays for PT, aPTT, and d-dimers require platelet-poor plasma, whereas thromboelastography is performed on whole blood, thromboelastography provides a more accurate representation of coagulation and allows the identification of hypocoagulable, hypercoagulable, and hyperfibrinolytic states. Conflicting information has been reported about the effects of age and sex on thromboelastography in humans and animals. Human studies have reported significant effects of age and sex on thromboelastography more often than have animal studies, but few publications are available about thromboelastography in the nonhuman primate and laboratory animal literature. We used a sample of 50 pigtail macaques (Macaca nemestrina) to determine whether age or sex influence thromboelastography values. Of 5 measured and 2 calculated variables produced by thromboelastography, sex had a significant effect only on the lysis-30 parameter, which also showed significant interaction between age and sex; values increased with age in male macaques but decreased with age in female macaques. In addition, we used the data to define reference intervals for thromboelastography parameters in pigtail macaques.